2022
DOI: 10.3389/fpubh.2022.802810
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Knowledge, Awareness, Practice, and Health Symptoms in Farmers Who Applied Organophosphates and Pyrethroids on Farms

Abstract: ObjectiveThis cross-sectional study aimed to examine farmers' knowledge, awareness, practices regarding pesticide use, and prevalence of health symptoms related to pesticides exposure among farmers who applied organophosphates (OP) and pyrethroids (PY).MethodsData regarding demographic variables and health symptoms pertinent to pesticide use was collected from 67 farmers who applied OP and 50 farmers who applied PY using interviews from January to March 2021.ResultsThe farmers who applied OP had lower knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 60 publications
0
2
0
3
Order By: Relevance
“…Resultados similares fueron publicados por Hutter et al (2021), quienes hallaron diferencia no significativa para estas variables entre agricultores expuestos a plaguicidas y agricultores de productos orgánicos, no expuestos a plaguicidas, ambos grupos residenciados en la misma zona. La tos es uno de los síntomas más frecuentemente reportados por la población agrícola (Rozzo y Pérez, 2020), principalmente la expuesta a insecticidas organofosforados (Thammachai et al, 2022), debido a que el incremento de la acetilcolina producida por estos plaguicidas afecta la función pulmonar, al actuar en los receptores muscarínicos periféricos, en los receptores nicotínicos de los músculos respiratorios y centros cerebrales superiores, y por efecto tóxico directo en la membrana de los alvéolos (Giyanwani et al, 2017).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Resultados similares fueron publicados por Hutter et al (2021), quienes hallaron diferencia no significativa para estas variables entre agricultores expuestos a plaguicidas y agricultores de productos orgánicos, no expuestos a plaguicidas, ambos grupos residenciados en la misma zona. La tos es uno de los síntomas más frecuentemente reportados por la población agrícola (Rozzo y Pérez, 2020), principalmente la expuesta a insecticidas organofosforados (Thammachai et al, 2022), debido a que el incremento de la acetilcolina producida por estos plaguicidas afecta la función pulmonar, al actuar en los receptores muscarínicos periféricos, en los receptores nicotínicos de los músculos respiratorios y centros cerebrales superiores, y por efecto tóxico directo en la membrana de los alvéolos (Giyanwani et al, 2017).…”
Section: Discussionunclassified
“…Adicionalmente, Thammachai et al (2022) reportaron que en agricultores aplicadores de organofosforados la frecuencia de alteraciones digestivas duplicó la referida por agricultores expuestos a plaguicidas piretroides.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…The serious health problems related to pesticide exposure in developing countries occur because of insufficiently qualified institutions governing and evaluating their production and sales [14,147,148]. Moreover, developing countries lack strict laws and regulations that properly regulate pesticide exports and imports [125,149]. As an example, Atreya et al [150] showed that it is crucial and necessary to set strict regulations to control farming practices in Nepal because farmers continue to buy highly toxic, obsolete pesticides.…”
Section: General Health Problems Associated With Pesticide Exposure I...mentioning
confidence: 99%
“…Other key characteristics are described in Table 1 [ 4 , 5 , 19 ]. This work focused on the classification of pesticides based on their chemical compositions ( Figure 1 ) and their target organisms in H, I, FN, A, and R [ 4 , 5 , 19 , 20 , 21 ].…”
Section: General Characteristics Of Pesticidesmentioning
confidence: 99%